Euro-Par 2016 : Parallel Processing Workshops : Euro-Par 2016 International Workshops, Grenoble, France, August 24-26, 2016, Revised selected papers /: Parallel Processing Workshops : Euro-Par 2016 International Workshops, Grenoble, France, August 24-26, 2016, Revised selected papers. (2017) - Unknown
No abstract available